(3GdEMUGA hGdGMJeGdGJ hHMhK GdYedjGJ (B/s - (3YLhQ, eMehO Ydj eJhdjs ((3GdbGgQI(B: s (3OGQ GdTjej(B, s, 2009)
(3jVe fXQjI GdGMJeGdGJ hGdGMUGA, fXQjI GdaFGJ, GdJLQHI GdYThGFjI , GdeJZjQGJ GdYThGFjI , GdebGjjS GdChdjI ddfRYI GdeQcRjI , HMhK GdYedjGJ , WQb GJNGP GdbQGQ, fXQjI GdOhGFQ , CSdhH HhQJ , GdHQeLI GdNWjI , eYGOdI GdNW GdeSJbje , eTGcd Gdfbd hGdJNUU, WQb Jbjje CSGdjH GdJfHDs
Keywords: (3GdEMJeGdGJs; (3GdEMUGA (B- (3GdeYGedGJ GdEQJHGWjI s; (3GdEMUGA GdQjGVjs; (3HMhK GdYedjGJs